2016
DOI: 10.1097/sla.0000000000001533
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Mechanical Ventilation Versus High-frequency Oscillatory Ventilation for Congenital Diaphragmatic Hernia

Abstract: Our results show no statistically significant difference in the combined outcome of mortality or BPD between the 2 ventilation groups in prenatally diagnosed congenital diaphragmatic hernia infants. Other outcomes, including shorter ventilation time and lesser need of extracorporeal membrane oxygenation, favored conventional ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(155 citation statements)
references
References 31 publications
7
144
0
4
Order By: Relevance
“…48 The recently published VICI trial failed to show any difference in CDH outcome between extracorporeal life support and non-extracorporeal life support centres. 27 Current extracorporeal life support practice patterns in Canada show very low rates of use compared with the United States and Europe, yet CDH outcomes across Canada are comparable with those of published international reports. [49][50][51] Extracorporeal life support should be discussed during prenatal counselling and may be considered as a therapeutic rescue option in those centres that offer it.…”
Section: In Circumstances Where Extracorporeal Life Support Is Considsupporting
confidence: 64%
See 1 more Smart Citation
“…48 The recently published VICI trial failed to show any difference in CDH outcome between extracorporeal life support and non-extracorporeal life support centres. 27 Current extracorporeal life support practice patterns in Canada show very low rates of use compared with the United States and Europe, yet CDH outcomes across Canada are comparable with those of published international reports. [49][50][51] Extracorporeal life support should be discussed during prenatal counselling and may be considered as a therapeutic rescue option in those centres that offer it.…”
Section: In Circumstances Where Extracorporeal Life Support Is Considsupporting
confidence: 64%
“…27 This study showed similar rates of mortality and bronchopulmonary dysplasia, the primary study outcome, between groups with conventional mechanical ventilation and groups with high-frequency oscillatory ventilation. Infants who were managed with conventional mechanical ventilation also had shorter durations of ventilation, reduced inotrope requirements and lower rates of extracorporeal life support.…”
Section: B-nr)mentioning
confidence: 67%
“…The optimal initial ventilation strategy was investigated in a collaborative initiative from the CDH EURO Consortium (VICI-trial, NTR 1310) [30]. Although the primary outcome (death/bronchopulmonary dysplasia at day 28) was not significantly different between the two groups, it was found that infants initially ventilated by conventional mechanical ventilation required a significantly shorter duration of ventilation, had less need for inhaled nitric oxide (iNO) or sildenafil, had a shorter duration of vasoactive medication and were less likely to require ECMO [3]. Therefore, the CDH EURO Consortium recommends conventional mechanical ventilation as the initial ventilation strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in opinion were primarily discussed between the five experts until full consensus was reached, and thereafter consensus was reached between all participating centers. The final consensus statement, therefore, represents the opinion of all participating centers based on the interpretation of the recent literature from 2010 to 2015 and includes the main findings of the so-called VICI-trial [3]. A consensus meeting, in which neonatologists, pediatric intensivists, gynecologists, prenatal physicians, pediatric surgeons, pediatric cardiologists and general pediatricians from 22 centers participated, was organized to discuss the most controversial recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…The SNAP takes only 2-4 minutes to calculate. The SNAP 2 score is considered independent of initial ventilation strategy [34].…”
Section: Herniamentioning
confidence: 99%